Plan de marketing internacional para la asociación artesanal de San Antonio de Ibarra - Sampedro, Ángel J. (2019)
The present project called “INTERNATIONAL MARKETING PLAN FOR INTRAPROFESSIONAL ASSOCIATION OF SAN ANTONIO DE IBARRA” aims to present an alternative solution that is focused on the diversification of new markets for its products and with it the increase in sales. This plan was developed based on two areas, bibliographic and field research. As for the first, it has to do with all the theoretical foundations related to: definitions, objectives, characteristics, classification and structure of each of the components of the marketing plan. The second refers to the application of an interview allowed us to identify that the association. The result obtained in the interview allowed us to identify that the association is in a critical situation since it does not have an alternative method of marketing to help increase its sales. Likewise, the negative aspects were identified: lack of promotion through technological tools, the same ones that served to formulate the proposal. Regarding the methodologyused, the methods, inductive, deductive and analytical were applied and as techniques the survey, interview and observation were applied. Therefore, the proposed marketing plan is aimed at presenting the product within the Colombia market, improving its corporate image to its customers and its environment, increasing promotions and the applications of new advertising strategies where priority is given to the use of communication technologies. At the end are the conclusions, recommendations, bibliography and annexes.